The Fisher's hedge hypothesis: What about homogeneity and~stability properties? - Malika Neifar; Amira Harzallah (Journal of Derivatives and Quantitative Studies: Seonmul yeon'gu (JDQS), 2024)
The purpose of this study is to see if the Fisher's hypothesis validation is robust in year or/and countries dimensions. We investigate whether nominal or real stock market returns are hedged against inflation rate, so as to determine the appropriate time and markets to invest in (from the 32 countries) over a period covering the 2008 global finance crisis (GFC) and the Covid 19 outbreak. Hedging property is found to be homogenous within countries and stable in time. Using either nominal or real return, based on cross-sectional data results, Fisher's hypothesis is generally validated with a few exceptions, while the time-series based results show that the hedge property is robust only in some countries. Using time series data (cross section data), in terms of homogeneity (homogeneity and stability), there is no difference between hedge property between Euro and non-Euro countries (groups of countries or between sub-periods) for both periods covering either 2008 GFC or the Covid 19 outbreak. Robust results are also the outcome of panel data investigations with or without the interest rate role as macro control variable.
Keywords: E44; G11; G15; 330; 2008 global financial crisis; Covid 19 outbreak; Cross-sectional; Fisher hypothesis; Panel data; Stability and homogeneity of hedging property; Time series